The Dual Role of cGAS-STING Signaling in COVID-19: Implications for Therapy - Daniele Castro di Flora; João Paulo Zanardini Lara; Aline Dionizio; Marília Afonso Rabelo Buzalaf (Cells)
The progression of COVID-19 involves a sophisticated and intricate interplay between the SARS-CoV-2 virus and the host’s immune response. The immune system employs both innate and adaptive mechanisms to combat infection. Innate immunity initiates the release of interferons (IFNs) and pro-inflammatory cytokines, while the adaptive immune response involves CD4+ Th lymphocytes, B lymphocytes, and CD8+ Tc cells. Pattern recognition receptors (PRRs) recognize pathogen-associated molecular patterns (PAMPS) and damage-associated molecular patterns (DAMPs), activating the cyclic guanosine monophosphate-adenosine monophosphate synthase-stimulator of interferon genes (cGAS-STING) signaling pathway, a crucial component of the innate immune response to SARS-CoV-2. This pathway fulfills a dual function during infection. In the early phase of infection, the virus can suppress cGAS-STING signaling to avoid immune detection. However, in the late stages, the activation of this pathway may trigger excessive inflammation and tissue damage, exacerbating disease severity. Modulating the cGAS-STING pathway, whether through agonists like dimeric amidobenzimidazole (diABZI) or inhibitors targeting viral proteins, such as 3CLpro, for example, offers a promising approach for personalized therapy to control the immune response and mitigate severe inflammation, ultimately improving clinical outcomes in patients with severe COVID-19.